2008
DOI: 10.1080/01421590801932228
|View full text |Cite
|
Sign up to set email alerts
|

Advanced 3D visualization in student-centred medical education

Abstract: Background: Healthcare students have difficulties achieving a conceptual understanding of 3D anatomy and misconceptions about physiological phenomena are persistent and hard to address. 3D visualization has improved the possibilities of facilitating understanding of complex phenomena. A project was carried out in which high quality 3D visualizations using high-resolution CT and MR images from clinical research were developed for educational use. Instead of standard stacks of slices (original or multiplanar ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 23 publications
4
65
0
6
Order By: Relevance
“…Evidence also suggests that computer-based teaching materials are associated with a better understanding of spatial anatomy (Petersson et al, 2009;Silén et al, 2008) and improved learning (Lynch et al, 2001;St Aubin, 2001;McNulty et al, 2004McNulty et al, , 2009Sugand et al, 2010). Furthermore, they have proved to be well received by students (Nieder et al, 2000;McNulty et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also suggests that computer-based teaching materials are associated with a better understanding of spatial anatomy (Petersson et al, 2009;Silén et al, 2008) and improved learning (Lynch et al, 2001;St Aubin, 2001;McNulty et al, 2004McNulty et al, , 2009Sugand et al, 2010). Furthermore, they have proved to be well received by students (Nieder et al, 2000;McNulty et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial ability is a good predictor of successful anatomy learning and evidence from this study suggests that only certain aspects of spatial ability can be gained through experience. Current educational methods, such as dissection, and more recently 3D computer images, have been shown to produce a better understanding of spatial anatomy (Crisp, 1989;Hill and Anderson, 1991;Pabst, 1993;Marks, 1996;Silén et al, 2008;Petersson et al, 2009). In the light of 13 the results from this study it may be possible to develop 'spatial ability' sessions, which at various points in the curriculum enable students to refine their spatial skills in order to enable more effective learning of anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Dewey (1910) suggests that when one is doing something, they are forced to use eyes, ears and sense of touch as guides for action which, as much as possible, has to be addressed in the design process. Researchers have suggested that the simulator's ability to give feedback provides individualized perceptual and cognitive support for the student's learning of a new skill (Nilsson, 2007;Rieber, Tzeng, & Tribble, 2004;Silén, Wirell, Kvist, Nylander, & Smedby, 2008). CAST, working as a scaffolding resource, provides a more able partner in Luckin's terms, and provided for improvisation, discovery and testing (Schön, 1983(Schön, , 1987.…”
Section: The Computer Simulation Resource (Tool)mentioning
confidence: 99%
“…In order to develop a computer-based instructional program that can successfully facilitate the process of learning anatomy, there is a need to focus on designing programs which can provide realistic graphics, flexible learning environments, and that follow principles of learning described in cognitive science (Issenberg, et aI., 2005;Silen, Wirell, Kvist, Nylander, & Smedby, 2008).…”
Section: Introductionmentioning
confidence: 99%